Evidence of sub-optimal sleep in adolescent Middle Eastern academy soccer players which is exacerbated by sleep intermission proximal to dawn - Fowler, P. M.; Paul, D. J.; Tomazoli, G.; Farooq, A.; Akenhead, R.; Taylor, L. (European Journal of Sport Science, 2017)
The purpose was to assess sleep patterns, quantity and quality in adolescent (16.2 ± 1.2 yr) Middle Eastern academy soccer players (n = 20) and the influence of an intermission upon these characteristics. On a 17-day training camp (located one time zone west of home) including three discrete matches, sleep was assessed pre- (PRE) and post-match (POST) via wrist actigraphy. Retrospective actigraphy analysis identified sleep characteristics, including if players experienced a sleep intermission (YES) or not (NO) proximal to dawn, and bedtime (hh:mm), get-up time (hh:mm), time in bed (h), sleep duration (h) and sleep efficiency (%). Within YES two bouts were identified (BOUT1 and BOUT2). No differences were seen between PRE and POST, nor between BOUT1 and BOUT2 (p > .05). Overall players did not meet National Sleep Foundation (NSF) guidelines (7:04 ± 1:16 h vs. recommended 8-10 h for 14-17 yr). Sleep duration was significantly reduced (~ -13% or -1:06) in YES compared to NO (6:33 ± 1:05 vs. 7:29 ± 1:17, p < .01). Despite players in YES waking earlier due to an intermission, they did not compensate for this with a later wake time, rising significantly earlier compared to NO (09:40 ± 00:38 vs. 10:13 ± 00:40, p < .05). These players on average do not obtain sufficient sleep durations relative to NSF guidelines, with decrements increased by an intermission proximal to dawn. High inter- and intra-individual variance in the players sleep characteristics indicates the need for individualized sleep education strategies and interventions to promote appropriate sleep.